Multiagent System Technologies 14th German Conference, MATES 2016, Klagenfurt, Österreich, September 27-30, 2016. Proceedings - Klusch, Matthias; Unland, Rainer; Shehory, Onn; Pokahr, Alexander; Ahrndt, Sebastian (Lecture Notes in Artificial Intelligence, 2016)
This book constitutes the proceedings of the 14th German Conference on Multiagent System Technologies, MATES 2016, held in Klagenfurt, Austria, in September 2016. 12 long papers and 5 short papers were carefully reviewed and selected from 28 submissions. MATES 2016 conference talks covered a broad area of topics of interest including MAS engineering and modeling, issues of human-agent interaction, collaboration and coordination, agent-based adaptation and optimization, and applications of MAS, in particular in the smart energy domain.